Deportations in the Nazi Era Sources and Research - Borggräfe, Henning; Jah, Akim (Arolsen Research Series, 2022)
During the Nazi era, about three million Jews and tens of thousands of Sinti and Roma were deported to ghettos, camps, and extermination centers, where most of them were murdered. In over 20 contributions, scholars from different countries examine the deportations through a variety of perspectives and questions, with a special emphasis on the discussion of historical source material.